Inflammatory breast carcinoma: prognostic factors associated with survival in a tertiary hospital in Central-West Brazil - Barros, Jordana Joab Alencar; Fuschino, Carolina de Miranda Henriques; Barbalho, Daniel Meirelles (Mastology, 2026)
Objectives: The primary objective of this study was to identify factors associated with survival in patients with inflammatory breast cancer undergoing surgical treatment at the Hospital de Base do Distrito Federal. Our secondary objectives were to define the epidemiological and clinical profile of these patients, evaluate the pathological staging, identify the rate of locoregional and distant recurrences, deaths, and estimate disease-free survival and overall survival. Methods: A retrospective cohort study was performed with 68 patients treated between 2013 and 2023. Analyses included Cox regression to determine factors associated with recurrence and mortality, using the hazard ratio as a measure of effect, and Kaplan-Meier curves to assess survival, considering p<0.05 as statistically significant. Results: The median age of patients was 50.5 years, with 47% under 50 years. The most prevalent tumor subtype was triple negative (39.7%), and the most common clinical staging was IIIB N1 (48.5%). The pathological complete response rate was 22.0%. The median follow-up was 1.4 years; locoregional recurrence occurred in 22.0% of patients; 47.5% had distant recurrence; and mortality reached 47.06%. The median survival time was approximately 3.8 years, and the median disease-free time was approximately 2.0 years. Factors associated with a worse prognosis for overall survival and disease-free survival in the multivariate analysis included triple-negative tumor (p=0.001 and p=0.020, respectively), and axillary ypN2/N3 (p<0.001 and p<0.001, respectively). In univariate analysis, residual tumor size (p=0.0199) and the presence of angiolymphatic invasion (p=0.0036) were also associated with a worse prognosis. Conclusion: The study emphasizes the need for early and multidisciplinary treatment of inflammatory breast cancer. Better pathological response and locoregional control are crucial for prognosis, especially in the triple-negative subtype.